Certain Aspects of the Civil Code's Article 816 Regarding Circumstances Affecting Likelihood of an Insurance Accident - Gryglewska, Ewa (Acta Universitatis Lodziensis. Folia Oeconomica, 2013)
This paper discusses certain aspects of the Civil Code's Article 816 and modifications to likelihood of insurance accident from the viewpoint of insurance practice which are indicated there. A range of examples from everyday relations between policyholders and insurers are presented against the background of the legal framework and considering practical difficulties associated with imperfection of the relevant regulations. Inaccuracy of the regulation's terms such as: a substantial change in likelihood of an accident or a corresponding change of premium are emphasised, where the law does not specify an entity to determine such characteristics. Stress is laid on the dubious negotiating opportunities available to policyholders as to premium changes after the likelihood of accident changes, since the regulation only allows for 14 days of contract notice without leaving much space for the parties to negotiate. The regulation is criticised for failing in practice to solve problems of parties to an insurance contract relative to changes of insurance and leaving most cases to be decided by way of litigation. Space afforded by the paper format only allows for discussion of some aspects of the regulation in question and the changing likelihood of accident it implies virtually without reference to jurisprudence, which is extremely scant, particularly with regard to the current version of the regulation, in force since 2007.